The RNA-binding protein Secisbp2 differentially modulates UGA codon reassignment and RNA decay - Fradejas-Villar, Noelia (Nucleic Acids Res, 2017)
Dual-assignment of codons as termination and elongation codons is used to expand the genetic code. In mammals, UGA can be reassigned to selenocysteine during translation of selenoproteins by a mechanism involving a 3΄ untranslated region (UTR) selenocysteine insertion sequence (SECIS) and the SECIS-binding protein Secisbp2. Here, we present data from ribosome profiling, RNA-Seq and mRNA half-life measurements that support distinct roles for Secisbp2 in UGA-redefinition and mRNA stability. Conditional deletions of the Secisbp2 and Trsp (tRNA(Sec)) genes in mouse liver were compared to determine if the effects of Secisbp2 loss on selenoprotein synthesis could be attributed entirely to the inability to incorporate Sec. As expected, tRNA(Sec) depletion resulted in loss of ribosome density downstream of all UGA-Sec codons. In contrast, the absence of Secisbp2 resulted in variable effects on ribosome density downstream of UGA-Sec codons that demonstrate gene-specific differences in Sec incorporation. For several selenoproteins in which loss of Secisbp2 resulted in greatly diminished mRNA levels, translational activity and Sec incorporation efficiency were shown to be unaffected on the remaining RNA. Collectively, these results demonstrate that Secisbp2 is not strictly required for Sec incorporation and has a distinct role in stabilizing mRNAs that can be separated from its effects on UGA-redefinition.